Antioxidant Activity of Pomegranate Husk Ellagitannins in Enhancing Oxidative Stability of Canola Oil During Frying - Mariela R. Michel; Maritza Pacheco-Lara; Romeo Rojas; Guillermo Cristian G. Martínez-Ávila; Juan Alberto Ascacio-Valdés; Mayra Aguilar-Zárate; Pedro Aguilar-Zárate (Foods)
This study evaluated the antioxidant efficacy of ellagitannins from a pomegranate husk in preventing vegetable canola oil (VCO) oxidation during French fry preparation. Ellagitannins were extracted using 80% acetone, purified via Amberlite XAD-16 resin chromatography, and incorporated into VCO at 0.05%, 0.1%, and 0.2% concentrations. VCO oxidation was assessed at 145 °C, 160 °C, and 190 °C, with frying experiments conducted at 160 °C for five 10 min cycles. Primary lipid oxidation (peroxide values) was measured using the AOCS Cd 8-53 method, and molecular structural changes were analyzed by infrared spectroscopy. Results showed that ellagitannins significantly mitigated VCO oxidation across all temperatures, with 0.05% identified as the optimal concentration. This concentration reduced peroxide values to 4.66 ± 1.15 meq O/kg, remaining stable and below acceptable limits during frying. Infrared spectroscopy confirmed no significant structural changes in VCO. These findings highlight ellagitannins as effective antioxidants for enhancing VCO oxidative stability during frying, offering a natural, sustainable solution for improving oil quality and extending its usability in the food industry.